Optimizing medium composition for TaqI endonuclease production by recombinant Escherichia coli cells using response surface methodology - TOKSOY ÖNER, EBRU (ELSEVIER SCI LTD, 2005)
The effect of medium composition on the TaqI endonuclease production, by recombinant Escherichia coli cells carrying a plasmid encoding TaqI endonuclease, was investigated using response surface methodology. The concentration of glucose, di-ammonium hydrogen phosphate, potassium di-hydrogen and magnesium sulphate in media were changed according to a central composite rotatable design consisting of 29 experiments and enzyme yields were determined. The results were fitted to a second order polynomial with an R-2 of 0.828. The model equation was then optimized using the Nelder-Mead simplex method to maximize enzyme yield within the experimental range studied. The optimum medium composition was found to be 6 g L-1 glucose, 1.5 g L-1 (NH4)(2)HPO4, 8 g L-1 KHPO4, and 0.8 g L-1 MgSO4 center dot 7H(2)O. The model prediction of 179 x 10(6) U g DCW-1 enzyme yield at optimum conditions was experimentally verified. This value is higher than any value obtained in the initial experiments as well as in the previously reported studies. The response surface methodology was found to be useful in improving the production of recombinant TaqI endonuclease in E. coli. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: TaqI endonuclease; medium design; recombinant enzyme production; response surface methodology; statistical optimization; RESTRICTION-ENDONUCLEASE; OPTIMIZATION; EXPRESSION